Simplified Crushing Analysis of Thin-Walled Columns and Beams - Ambramowicz, W. (Engineering Transactions, 1981)
An approximate method is developed for calculating the strength and energy absorption of thin-walled beams and columns with, rectangular, square, closed-hat and “u” shape cross sections. Three basic deformation mechanisms are distinguished and the mean crushing force and bending resistance- is determined. The present solution is compared with existing experimental data. In all cases good agreement is obtained.